PENDIDIKAN KARAKTER DALAM AUTOBIOGRAFI HABIBIE & AINUN KARYA BACHARUDDIN JUSUF HABIBIE - MEGA DWI LESTARI; Elmustian Rahman; M. Nur Mustafa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research discusses the characters education in Habibie & Ainun Autobiograph by Bacharuddin Jusuf Habibie. In the Habibie &Ainun Autobiograph many a lot of characters education, so according the author that needs to be researched. The problems in this research is about character education aspect that is divided 18 character education. The theory is used by Kemendiknas. The method used by in this research is qualitative research method with approarch analysis descriptive. Based on this research result, author found that 64 datas, that’s : (1) 8 datas on Religious aspect, (2) 2 datas on truthful aspect, (3) 2 datas on tolerancy aspect, (4) 1 datas on discipline aspect, (5) 11 datas on hard work aspect, (6) 4 datas on creatif aspect, (7) 6 datas on independent aspect, (8) 2 datas on democratic aspect, (9) 2 data on coriousity aspect, (10) 4 datas on spirit nasionality aspect, (11) 5 datas on love of country aspect (12) 2 datas on appreciate aspect, (13) 3 datas on friendly aspect, (14) 1 datas on peaceable aspect, (15) 2 datas on avid reader aspect, (16) environment care aspect are no datas on environment care aspect, (17) 7 datas on sosial care aspect, (18) 2 datas on responsibility aspect. So the most datas is hard work aspect, religious, and sosial care. Based the research can concluded that the Habibie & Ainun Autobiograph many a lot of character education should be implement. Author suggest this research about character education need to developed, caused character education in autobiograph can serve as role model.